Socioeconomic Status of the Family as a Determinant of Family-School Cooperation - Mendelová, Eleonóra; Gužíková, Libuša; Zelená, Hana (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
Many factors on both the family and the school parts determine family-school cooperation. This paper presents the research results aimed at finding the relationship between family socioeconomic status and teacher cooperation at the primary level of education. The research findings present how parents rate their current cooperation with teachers at the primary level of education. The article also highlights whether there is a statistically significant association between parents' education, occupation, income and their satisfaction with the cooperation with the teacher. The research instrument was a questionnaire addressed to parents of children in primary education. The research findings were evaluated with mathematical-statistical methods: Pearson's chi-squared test, Kolmogorov-Smirnov test, and Kruskal-Wallis’ test. The research has shown that indicators of family socioeconomic status (education, income and occupation) do not differentially affect the evaluation of family-school cooperation, which was demonstrated by statistical analysis of research findings. Parents, regardless of their socioeconomic status (SES), expressed a positive attitude towards the class teacher, their satisfaction with cooperation, and perceived teachers' efforts to develop cooperation with the child's parents. Parent-teacher cooperation impacts the child's functioning in the institutional education setting. It is of particular importance at the primary level of education. It influences the process of adaptation of students to the school environment at the beginning and later their learning success and relationship to the school.